Pengorganisasian Kurikulum dan Pembelajaran pada Sekolah Kejuruan di Lingkungan Pesantren - Ali, Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This paper explains about curriculum management activities in vocational schools within pondok pesantren (WPP). The focus of the discussion is on the orientation of the vocational school curriculum in pesantren and its implementation activities as well as how school leaders and pesantren leaders influence the curriculum implementation organization (OPK) in schools WPP. The aim is to find the orientation, strategy and approach of OPK activities in vocational schools WPP. This research used qualitative research with a case study design. Data was collected through in-depth interviews with leaders of Islamic boarding schools, school leaders, and teachers by purposive sampling, observation, and document analysis. The conclusion of this paper is the activities of OPK have led to innovation in curriculum management and learning in schools WPP. The OPK strategy uses Collaborative-collegial management with a democratic approach based on the noble values of pesantren and professionalism.